Language Errors in Explanatory Text Essay of Class VIII Students of Kedawung 2 Public Middle School - Ayuni, Ari Diah Nur; Sabardilla, Atiqa (Universitas Muhammadiyah Surakarta, 2023)
This research aims to determine the types of language errors at the spelling, morphology, and syntax levels in explanation texts written by class VIII students at Kedawung 2 Public Middle School. This type of research is qualitative with a descriptive design. Data collection techniques use documentation, observation, and data analysis. The results of the research show that in the explanatory text, there are 158 spelling errors, 116 capital letter errors, 29 errors in writing abbreviations, 10 errors in writing letters, and 3 errors in the use of punctuation marks. Morphology 4, 2 affixation errors, 2 reduplication errors. Syntax 6. Errors with sentence details. This research is oriented towards language errors so that it can When carrying out language activities, there will be mistakes in language. According to Pranowo (2018) (Albelr, 2018) a language error is something that deviates from the rules found in language use. An essay is a piece of writing that results from thoughts or ideas or communication with other people, the result of which is in the form of writing that is used as a written work. In an essay, there will be some linguistic errors. From the understanding of linguistic errors above, an analysis of linguistic errors is needed which can find out where the error occurs and carry out corrections. be used to prevent mistakes and be able to understand these mistakes.